Enhanced conductivity of bacterial cellulose films reinforced with NH4I-doped graphene oxide - Torres, F.G.; Ccorahua, R.; Arroyo, J.; Troncoso, O. (Taylor and Francis Inc., 2019)
Bacterial cellulose (BC) films reinforced with reduced graphene oxide (RGO) platelets were investigated to assess their potential application as solid polymeric electrolytes. BC-RGO composites were further doped with NH4I at different concentrations to evaluate the effect of NH4I doping on the conductivity. Scanning electron microscopy images confirmed that GO addition did not alter BC coherent three-dimensional morphology. Electrochemical impedance spectroscopy studies revealed that the ionic conductivity increased with the ammonium iodide salt concentration. The highest conductivity found was 1.32 × 10−4 S/cm for the samples doped with 5% NH4I, suggesting that BC-RGO can be a promising candidate for electrochemical applications.
Keywords: Bacterial cellulose; Reduced graphene oxide; Solid polymeric electrolytes; https://purl.org/pe-repo/ocde/ford#2.10.00